Maria Messina : her works - Gochin, Lara Shantal (University of Cape Town, 2015)
Includes bibliographical references. === In this thesis I examine the work of the tum-of-the century Sicilian writer, Maria Messina (1887-1944). Relatively prolific, she received attention from some of the major critics of her day. But her works were forgotten after her death until the early 1970s. Messina's works are significant for their contribution to the understanding of both women's literature and the position of the woman in a patriarchal society during the period of Fascist control of Italy. Although there is growing interest in Messina's works, no full-length study exists which combines a general overview of her writings in their historical and cultural context with an accurate biographical history, which also includes unpublished and rare documents by and on Messina. This thesis fills this gap. All available criticism of Messina's writings, both from the early Twentieth century and from the last twenty years has been taken into account. This comprises the overlooked and forgotten reviews from journals and newspapers as well as the recent German and American ones. The corpus of the known works by Messina has been increased by tracing unknown publications in literary journals of the 1910s and 1920s. Messina's known published correspondence has been increased by the discovery of her unpublished letters to Alessio DiGiovanni, which span the years 1910-40, and those to Enrico Bemporad. The former provide new knowledge of her life, cultural formation and social interaction. The latter serve as documents for her publishing history and her private life in general. A more historically accurate picture of Messina's life and work can now be formed, not only from the unpublished letters but also from the documents and certificates obtained from archives and municipal records. On the strength of internal and external evidence, not previously taken into account, a detailed biography and personality sketch of Messina and an assessment of her cultural and literary formation have now been provided. The literary analysis examined Messina's short stories and novels on a separate basis, while taking into account certain themes which were central to both genres. Rediscovered short stories were found to contribute greatly to a balanced understanding of Messina's subject matter: the tormented mother-child relationship, the dichotomy between greed and need, the ambivalent stance towards love. The analysis of the novels also revealed new insight into Messina's attitude towards the female condition within society. The present feminist-oriented criticism on Messina has tended to overlook her ambiguous representation of the career-woman. Nor has it been aware of the progressive weakening and elimination of the authoritative male figure. These aspects have been seen to be the externalisation of Messina's attitude towards Fascism. In her historical context, on one level Messina appears to accept and transmit Fascism's idealisation of the wife and mother and the glorification of the rural and traditional ways of life. On another level she denounces Fascist doctrine by ridiculing its cardinal symbol of the virile male. While considering Messina's writings as important literary and sociological documents of the condition of the woman in a critical historical moment, the analysis of the text is not oriented from the sole perspective of feminist criticism, which would have been too restrictive. It is instead conducted from a general critical perspective, moving from the texts themselves in order to assess their structural, thematic, stylistic and symbolic components. Research was carried out in the principal libraries of Italy and those in which Messina resided - Rome, Florence, Urbino, Naples, Palermo, Catania, Pistoia - for published and unpublished material written on and by Messina. Searches for biographical information and documents were carried out in all the centres in which Messina lived. Family members and descendents of her friends were contacted. The material obtained was used to compile a biographical history and analyses of her writings.